2007
DOI: 10.1007/s00586-007-0458-z
|View full text |Cite
|
Sign up to set email alerts
|

The internal mechanical properties of cervical intervertebral discs as revealed by stress profilometry

Abstract: Extensive anatomical differences suggest that cervical and lumbar discs may have functional differences also. We investigated human cervical discs using ''stress profilometry''. Forty-six cadaveric cervical motion segments aged 48-90 years were subjected to a compressive load of 200 N for 20 s, while compressive 'stress' was recorded along the posterior-anterior midline of the disc using a pressure transducer, side-mounted in a 0.9 mm diameter needle. Stress profiles were repeated with the transducer orientate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 38 publications
4
44
1
Order By: Relevance
“…It is likely that a significant portion of the annulus thickness, in the radial direction, was included in the ROI: Skrzypiec et al (Skrzypiec et al, 2007) reported an average frontal thickness of about 7 mm for the annulus, which is similar to the thicknesses observed in b-mode image (Figure 1).…”
Section: Fig 5 (A)supporting
confidence: 60%
“…It is likely that a significant portion of the annulus thickness, in the radial direction, was included in the ROI: Skrzypiec et al (Skrzypiec et al, 2007) reported an average frontal thickness of about 7 mm for the annulus, which is similar to the thicknesses observed in b-mode image (Figure 1).…”
Section: Fig 5 (A)supporting
confidence: 60%
“…Data from studies on Earth show that some degree of cervical spine lengthening occurs with recumbency [26,27]. There are a number of differences between cervical and lumbar discs: in composition [28], anatomy [29] and biomechanical characteristics [30]. However, these data do not help us understand why the risk of IVD herniation is much more elevated at the cervical spine than at the lumbar spine in astronauts.…”
Section: What Are the Likely Mechanisms?mentioning
confidence: 99%
“…[18,19] In addition, the mechanical properties of xylitolbased elastomers correspond to biologically relevant values that fall close to or are equal to those of various tissues, such as acellular peripheral nerves, [20] small diameter arteries, [21] cornea [22] and intervertebral discs. [23] In this report, we have shown only three examples of possible polymers based on this monomer. Potential combinations for the chemical composition of xylitol-based polymers are numerous and therefore it provides a platform to tune mechanical properties, degradation profiles and cell attachment.…”
mentioning
confidence: 95%